Pengaruh Keberadaan SMK Keling Kumang Terhadap Minat Masyarakat Untuk Berinvestasi Ekonomi di Kabupaten Sekadau - darius damestuteles; Maria Junianta; Fitria Elvi (Jurnal Bisnis dan Kewirausahaan, 2023)
The existence of educational institutions in an area has various influences on the economic activities of the surrounding community. The existence of the Keling Kumang Vocational School which is located in Sekadau Regency influences the interest of the surrounding community, especially the people in the Sekadau City area. After conducting research and analysis, the results obtained show that there is a relationship that shows there is an interrelationship between the existence of Keling Kumang Vocational School and changes in people's interest in investing. The existence of Keling Kumang Vocational School is able to encourage the community to carry out various types of investment activities. The more advanced the Keling Kumang Vocational School, the more students of the Keling Kumang Vocational School, the more people who are interested in investing around the Keling Kumang Vocational School. The more people who invest shows more people are entrepreneurship so that they are able to create jobs for the surrounding community. This research examines how the existence of Keling Kumang Vocational School is able to influence the interest of the Sekadau community to invest in the environment around Keling Kumang Vocational School.